Analisa Kelayakan Rusunawa Tenayan Raya Berdasarkan Kemanpuan Masyarakat (Studi Kasus Rusunawa Tenayan Raya Pekanbaru) - Ayu Agustin Mahyas; Hendra Taufik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Tenayan Raya’s Flat-house is built for poor people to overcome the problems of housing in Pekanbaru. especially middle lower economics citizen. The research took place at sub-district of Tenayan Raya Pekanbaru where data were collected from the survey at three population sub-districts such as Tenayan Raya, Lima Puluh, and Sail. It were analyzed by using correlation, multiple linear regression, determination, and Z test to analyzed distance-location, facilities, income rates, tenant willingness to stay, and satisfaction of theirs current housing. The tenant-price will be analyzed by using some methods, like Benefit Cost Ratio (BCR), Net Present Value (NPV), Internal Rate of Return (IRR), Break Event Point (BEP) and sensitivity analysis. 300 respondents which consist of 64,67% laborers and their highest education background are 35% senior high school. As a result, the average capability-price of tenant based on their income are Rp. 487.000/month . It will fulfill 78% tenants from the full capacity of the flat. In addition, the target of Break Event Point will be reached by year 2056. In other word, the most affecting factor of the feasible-price is income rates, so that the government should pay more attention to this variable if they want to run flat-house.Keywords: Tenayan Raya’s flat-house, capability-price, feasibility study.